Effect of Multiradiance Low-Level Laser Therapy and Topical Silver Sulfadiazine on Healing Characteristics of Dermal Wounds in Marine Toads (Rhinella marina). (17th October 2020) - Archibald, Kate E.; Harrison, Tara; Troan, Brigid; Smith, Dustin; Minter, Larry J.
Abstract : Current recommendations for wound management in amphibians are based primarily on clinical experience and on extrapolation from other taxa, whereas controlled clinical studies are lacking. Low-level laser therapy, also termed photobiomodulation, has gained popularity in veterinary medicine and may represent a valuable adjunct therapy for wound care in amphibians, though dosing and safety evaluations have not been previously reported. Silver sulfadiazine (SSD), a topical antimicrobial, is commonly utilized in amphibian medicine but little is known about its effects on wound healing in this class of animals. This pilot study evaluated the effects of repeated treatments of low-level laser therapy or topical SSD on second-intention healing characteristics of surgically induced full-thickness dermal wounds in 33 adult wild-caught marine toads. Toads were anesthetized, and a 6 mm cutaneous biopsy was performed over the right dorsum. They were then randomly assigned to one of three groups: laser therapy (LT) at 5 Hz (905 nm wavelength on a super pulsed sequence), topical SSD (SD), or control sham treatment (CT). Treatments were administered at 24 hrs after biopsy and then every 72 hrs thereafter, concurrent with a visual assessment of the wound. Toads were euthanized at one of five timepoints (day 4, 7, 13, 19, or 28) to permit scoring of histologic criteria, including lymphocytic inflammation, granulomatous inflammation, heterophilic inflammation, granulation tissue, fibrosis, and reepithelialization. Visual assessments and histologic scoring did not identify a benefit of laser therapy or SSD as compared to controls. Laser therapy and SSD, at the doses and dosing schedule utilized in this pilot study, appear to be safe and well-tolerated treatments in marine toads, but may not be warranted for uncomplicated skin wounds in this species.